Discovery of Hydrothermal Vent Fields on Alarcón Rise and in Southern Pescadero Basin, Gulf of California. (12th December 2018) - Paduan, Jennifer B.; Zierenberg, Robert A.; Clague, David A.; Spelz, Ronald M.; Caress, David W.; Troni, Giancarlo; Thomas, Hans; Glessner, Justin; Lilley, Marvin D.; Lorenson, Thomas; Lupton, John; Neumann, Florian; et al.
Abstract: Hydrothermal vent fields located in the gap between known sites in Guaymas Basin and 21°N on the East Pacific Rise were discovered on the Alarcón Rise and in southern Pescadero Basin. The Alarcón Rise spreading segment was mapped at 1‐m resolution by an autonomous underwater vehicle. Individual chimneys were identified using the bathymetric data. Vent fields were interpreted as active from temperature anomalies in water column data and observed and sampled during remotely operated vehicle dives. The Ja Sít, Pericú, and Meyibó active fields are near the eruptive fissure of an extensive young lava flow. Vent fluids up to 360 °C from Meyibó have compositions similar to northern East Pacific Rise vents. The Tzab‐ek field is 850 m west of the volcanic axis, and active chimneys rise up to 33 m above a broad sulfide mound. The inactive field is 10 km north‐northeast along the rift axis, and most sulfide chimneys are enriched in Zn and associated elements that are transported at lower temperature compared to the more Cu‐rich active fields. In southern Pescadero Basin, the Auka field is on the margin of a sediment‐filled graben at 3, 670‐m depth. Discharging fluids are clear, contain hydrocarbons, and have neutral pH, elevated salinity, and temperatures up to 291 °C. They have deposited massive mounds of calcite with minor sulfide. The fluids are compositionally similar to those in Guaymas Basin, produced by high‐temperature basalt‐seawater interaction followed by reaction with sediment. The paucity of sulfide minerals suggests subsurface deposition of metals. Plain Language Summary: Hydrothermal chimneys on two previously unexplored spreading ridges, the Alarcón Rise and southern Pescadero Basin, were discovered on Monterey Bay Aquarium Research Institute expeditions to the Gulf of California. Autonomous underwater vehicles were used to map the region, followed by dives with remotely operated vehicles to observe and sample features on the seafloor. Many of the chimneys on the Alarcón Rise were found to be high‐temperature black smokers, so‐called because of the particles of metal‐sulfide that precipitate from the hot fluid as it cools. Deposited precipitates have built chimneys up to 33 m tall, composed of iron, copper, and zinc sulfides, and include some precious metals. The venting fluid was seawater that has been heated by, and interacted with, underlying basalt lavas through which it circulated. In the southern Pescadero Basin, hydrothermal fluids are clear and somewhat cooler than at the Alarcón Rise, and the chimneys are composed of calcite with little sulfide. These fluid and deposit compositions are most similar to those at the Guaymas Basin, located farther north in the Gulf of California, where the heated vent fluids pass through, and react with, thick sediments before exiting the seafloor. Key Points: Active hydrothermal chimneys were discovered at Alarcón Rise and Pescadero Basin in high‐resolution AUV data and sampled on ROV dives Black smoker fluids and sulfide‐rich deposits from Alarcón Rise resemble other basalt‐hosted fields Pescadero Basin fluids have interacted with sediment to produce hydrocarbons and have built chimneys and mounds of calcite with little sulfide